Fear of Being Laughed at in Borderline Personality Disorder - Brück, Carolin; Derstroff, Stephanie; Wildgruber, Dirk (Frontiers in Psychology, 2018)
Building on the assumption of a possible link between biases in social information processing frequently associated with borderline personality disorder (BPD) and the occurrence of gelotophobia (i.e., a fear of being laughed at), the present study aimed at evaluating the prevalence rate of gelotophobia among BPD patients. Using the Geloph<15>, a questionnaire that allows a standardized assessment of the presence and severity of gelotophobia symptoms, rates of gelotophobia were assessed in a group of 30 female BPD patients and compared to data gathered in clinical and non-clinical reference groups. Results indicate a high prevalence of gelotophobia among BPD patients with 87 % of BPD patients meeting the Geloph<15> criterion for being classified as gelotophobic. Compared to other clinical and non-clinical reference groups, the rate of gelotophobia among BPD patients appears to be remarkably high, far exceeding the numbers reported for other groups in the literature to date, with 30% of BPD patients reaching extreme levels, 37% pronounced levels, and 20 % slight levels of gelotophobia.